Digital learning platform and students satisfaction : Regression Analysis / Farah Syazreena Azmi, Norfadzilah Abdul Razak and Ayu Rohaidah Ghazali - Azmi, Farah Syazreena; Abdul Razak, Norfadzilah; Ghazali, Ayu Rohaidah (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2018)
Technology has no boundary, people made technology as their primary routine in daily task. Technology also mainly being used worldwide and provide many outcomes towards the education system. The transformation of industrial revolution 4.0 brings the education system one step forward to meet the worldwide demand. Students nowadays are Z-generation that live in modern and digital lifestyle. Thus, the digital platform such as E-Learning has been applied in recent of teaching and learning in most of the university. However, the application and usage of e-learning in university did not well used and applied by students. Hence, there is a need for e-learning platform to transform and improve the system so that student can be more interest to use E-learning and ultimately result in better academic performance. A theory of Technology Acceptance Model (TAM) applied as the fundamental of this study. Hence this study aims to investigate the perception of 152 students in selected of the local university towards the application of e-learning platform. Data collection further analysed using regression analysis and found perceive usefulness, perceived ease of use, behavioural intention and system usage predict significantly towards student satisfaction. The finding implies that the application of e-learning among students was satisfied. The improvement of the interaction system and attraction of the system can promote and encourage students active to use e-learning.